2016
DOI: 10.1080/15384101.2016.1138188
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinetic effects of Wee1 disruption in pancreatic cancer

Abstract: The Wee1 kinase, which is activated in response to DNA damage, regulates exit from G2 through inhibitory phosphorylation of Cdk1/Cdc2, and is an attractive drug target. However, recent work has highlighted effects of Cdk2 phosphorylation by Wee1 on movement through S-phase, suggesting the potential to sensitize to S-phase specific agents by Wee1 inhibitors. In this paper we applied multiparametric flow cytometry to patient-derived pancreatic cancer xenograft tumor cells to study the cell cycle perturbations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…WEE1, a member of the tyrosine kinase family, is a G2/M checkpoint regulatory protein involved in the regulation of cell cycle progression 27. Massive studies reported that WEE1 expression was upregulated in various tumors, and its oncogenic roles were also widely reported, which suggested that WEE1 may be a good therapeutic candidate target in cancer treatment 2830. In glioma, several studies reported that WEE1 was overexpressed in glioma and promoted glioma cells proliferation, migration, and invasion 31,32.…”
Section: Discussionmentioning
confidence: 99%
“…WEE1, a member of the tyrosine kinase family, is a G2/M checkpoint regulatory protein involved in the regulation of cell cycle progression 27. Massive studies reported that WEE1 expression was upregulated in various tumors, and its oncogenic roles were also widely reported, which suggested that WEE1 may be a good therapeutic candidate target in cancer treatment 2830. In glioma, several studies reported that WEE1 was overexpressed in glioma and promoted glioma cells proliferation, migration, and invasion 31,32.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, AZD1775 inactivated G 2 /M checkpoint to abrogate G 2 /M arrest induced by cisplatin (Figures 2(c), 2(d), and S2 ) [ 28 ], indicating DNA damage enhancement of AZD1775-cisplatin combination partially due to G 2 /M checkpoint abrogation in our work. Beyond replication stress initiated by G 2 /M checkpoint abrogation, AZD1775-induced DNA damage has also been attributed to AZD1775's effect on dephosphorylation and activation of CDK2 during S phase which regulates overall timing of DNA replication [ 11 , 30 ]. AZD1775 can cause deficiency in homologous recombination repair [ 31 ], which serves as another approach to AZD1775-induced DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, disputable opinions exist demonstrating that p53 status is indispensable for AZD1775's anticancer activity [ 10 , 19 , 24 ]. DNA damage rather than premature mitosis (a typical phenotype of G 2 /M checkpoint defects) has recently been proven to be the primary cytotoxic consequence of AZD1775 in some cases [ 11 , 30 ]. As mentioned above, apart from through a p53-reliant G 2 /M checkpoint defect, AZD1775 can also generate DNA damage-associated cytotoxicity through a p53-independent manner, such as homologous recombination defect and DNA replication disruption by inactivating CDK2 [ 11 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting our findings, Green module-overtargeted FBXO3 has been indeed reported to be downregulated in multiple cancers and to suppress cell proliferation partly through the degradation of cyclin D1 (65). On the other hand, the nuclear protein Wee1 (the product of the Green module-overtargeted WEE1 gene) was recently recognized as a tumor suppressor that regulates the progression of pancreatic cancer cells via delaying G2, which allows for longer time to repair post-replication errors in genomically unstable cancers (66). Similarly, the RB1 gene is mutated in a variety of human cancers and represents a classical prototype of tumor suppressor, inhibiting cell proliferation primarily through targeting of the E2F transcription factor and, additionally, through transcription-independent mechanisms (67).…”
Section: Discussionmentioning
confidence: 99%